(untitled) (Al-Aasar, 2025)
The Qur’ān is the primary source of Islamic law and guidance, encompassing principles related to faith, worship, ethics, and legal rulings. Among its contents, the verses that deal specifically with practical and legal injunctions, commonly known as Āyāt al-Aḥkām (verses of legal rulings), hold a central position in the development of Islamic jurisprudence. This research aims to examine the interpretation and classification of the Qur’ānic legal verses and to analyze the differing perspectives of Muslim jurists (fuqahāʾ) regarding these verses. The study highlights that juristic اختلاف (differences) arise mainly due to variations in principles of interpretation, linguistic analysis, contextual understanding, and methodologies of legal reasoning (uṣūl al-fiqh). Furthermore, the research explores how jurists have categorized these verses into various domains such as acts of worship, transactions, family law, and criminal law. The study concludes that juristic diversity in interpreting Āyāt al-Aḥkām reflects the flexibility, comprehensiveness, and adaptability of Islamic law, rather than contradiction, and plays a vital role in addressing the legal needs of different times and societies